The Role of Public Spending on Education, Health, and Economic Growth toward Human Development Index in the Local Economy - Dwi Nurvita; Siti Rohima; Abdul Bashir; Mardalena Mardalena (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study investigates the effect of economic growth, education expenditures, and health expenditures on human development index (HDI) in Jambi Province. This study used panel data of 11 district/cities from 2012 to 2019. The analytical approach was quantitative by applying panel data regression models. The findings of the study indicated that the economic growth, education expenditure, and health expenditure had a significant and positive influence on the human development index. The implication of the model in this study shows that the efforts made by the Jambi provincial government are effective and optimal in allocating education and health spending to encourage increased human capital as measured by a high human development index. This is input in structural reforms in the education and health sectors to ensure that skilled human resources are developed in areas critical to economic development.